2021
DOI: 10.1037/bul0000311
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of household chaos on child executive functions: A meta-analysis.

Abstract: Household chaos—characterized by disorganization and instability within the home—is inversely associated with child executive functioning and effortful control, although a quantitative synthesis of the findings is currently lacking. This meta-analysis incorporated 35 studies with 36 independent effect sizes including 16,480 children. Several moderators were assessed, the most fundamental involving method (i.e., informant-completed questionnaire vs. direct assessment) of assessing executive functions. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 108 publications
(170 reference statements)
3
35
0
2
Order By: Relevance
“…Household instability emerged as a potentially important adverse predictor of child executive functions both directly and indirectly via parental responsiveness. The direct association between household instability and child executive functions is aligned with other studies [ 17 , 20 , 75 ]. However, examination of the indirect effect has been sparse.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Household instability emerged as a potentially important adverse predictor of child executive functions both directly and indirectly via parental responsiveness. The direct association between household instability and child executive functions is aligned with other studies [ 17 , 20 , 75 ]. However, examination of the indirect effect has been sparse.…”
Section: Discussionsupporting
confidence: 86%
“…Separating the dimensions of household chaos demonstrated that instability, and not disorganization, had a negative association with child executive functions, both directly and via parental responsiveness. Greater chaos in the home has been previously linked to deficits in executive functions measured via direct assessments [10,15] and questionnaires [17,72]. Children may be withdrawing from uncontrollable environmental stimuli, in chaotic households [73], and while this may be protective against threats, it can constrain exposure to positive influences, thereby reducing opportunities for important interactions that promote executive function development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children in their second year may not have the capacity to filter out stressful stimuli created by chaotic environments, the cumulative effect of which could be the development of a rudimentary sense of ineffectiveness in controlling events within the home environment, particularly adverse events, and over time, disrupting the development of adaptive regulatory skills (Hardaway et al, 2012; Wachs & Evans, 2010). Alternatively, higher levels of HC may predispose children to shift attention away from overstimulating events in the environment and, in turn, reducing opportunities to benefit from potentially important aspects of socialization (Andrews et al, 2021; Evans, 2006). Chronic exposure to disorganization in one’s environment, especially during the developmental period when cognitive and emotional advances coincide with the emergence of long-term memory (Lukowski & Bauer, 2014), may result in becoming habituated to the chaotic environment, which may further debilitate healthy behavioral adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the distracting and overstimulating nature of chaotic environments may impede children's developing selfregulatory skills. A recent meta-analysis concluded household chaos and executive functions, like selfregulation, are signi cantly and inversely related [29]. Such relationships are important, as self-regulatory skills, including inhibitory control and emotion regulation, may be protective against childhood obesity development [30].…”
Section: Potential Pathways From Chaos To Obesitymentioning
confidence: 99%